Evaluation of Subsidence in Stand-Alone Cervical Cage: Incidence, Risk Factors and Effects on Clinical and Radiological Picture - Salah Hamada (Egyptian Spine Association, 2015)
Background Data: Anterior Cervical Discectomy and Fusion is the gold standard for treating cervical degenerative disc disease associated with radiculopathy and/or myelopathy. When indicated, surgery can achieve neural tissue decompression and biomechanical stabilization through bony fusion. One of the known complications of stand-alone anterior cervical cage is cage subsidence. Published literature however, contains mixed results in terms of rate of cage subsidence, loss of lordosis and its clinical effects. Purpose: We report our experience in stand-alone anterior cervical cage, our subsidence rate and its effect on loss of lordosis and clinical picture Study Design: Retrospective clinical case study. Patients and Methods: we inserted seventy-two cervical cages (in fifty patients), who had Anterior Cervical Discectomy and Fusion using a stand-alone polyetheretherketone (PEEK) cage under our care. We recorded the self-reported Visual Analogue Score for arm and neck pain and measured the total intervertebral height/disc space or cage ratio, segmental Cobb angle, the distance between the anterior rim of the cage and the anterior vertebral body line, superior or inferior end plate violation and anterior or posterior cage migration on lateral X ray film preoperatively and on each follow up visit (day 1, 7-21 days, 3, and 6 months). Results: Our cage subsidence rate in the studied sample was 23.6% in 6 months (17 out of 62 cages subsided). We found a statistically significant correlation between immediate postoperative disc height and subsidence (the more distraction we applied to the disc space the more likely subsidence would happen). Cage subsidence did not increase the incidence of recurrence of radicular, myelopathic symptoms or neck pain although it resulted in significant loss of the segmental Cobb angle. Conclusions: Disc space over-distraction in stand-alone anterior cervical cage significantly increases the risk of subsidence. Subsidence significantly affects the segmental Cobb angle but not the clinical outcome. (2015ESJ077)